Stakeholder engagement as a dynamic capability. Issue 2 (18th September 2019) - Panda, Swapna Sonali; Sangle, Shirish
Abstract: How can some firms gain and manage competitive advantage over their peers? In a dynamic scenario, what makes a firm stand out from its competitors? This paper attempts to answer these questions by taking a dynamic capability lens and proposing that stakeholder engagement is a key reason for a firm to attain competitive advantage. This paper attempts to explain how and why stakeholder engagement is a dynamic capability by establishing (a) stakeholders as a resource, (b) capability required to explore this resource, and (c) dynamics of the firm–stakeholder relationship. Finally, this paper describes the four different strategies adopted by the firm, namely, reactive, defensive, accommodative, and proactive, and recommends the suitable stakeholder engagement techniques for each of these strategies.